Pelatihan Aplikasi Berbasis Web Pada SMK Teladan Pematangsiantar Sebagai Upaya Meningkatkan Kemampuan Vokasi - Widodo Saputra; Jaya Tata Hardinata; Harly Okprana (LPPM STIKOM Tunas Bangsa, 2020)
Internet is the media that has the most up to date information. Now as time grows many web-based applications that can be used as needed. The increasing development of technology is the growing number of human resource needs that are reliable and creative that can provide the latest innovations that can help to suit the needs. The young generation is a very competent generation to be a reliable human resource for example is students. To improve the quality of students to technological developments need to be held special vocational training program. This training Program provides a good impact on students. From pre test results and post test can be seen before training until after training. The results after the training increased rapidly so that it can be concluded through this training the ability of students in the field of vocational get good results